2023
DOI: 10.1093/ofid/ofad018
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus DNAemia Requiring (Val)Ganciclovir Treatment for More Than 8 Weeks Is a Key Factor in the Development of Antiviral Drug Resistance

Abstract: Background Prolonged (val)ganciclovir [(V)GCV] exposure for ≥ 6 weeks is a known predisposing factor for cytomegalovirus (CMV) drug resistance. However, the selection of this threshold was based on limited data. Here, we sought to reappraise the risk factors for the development of (V)GCV resistance through a specific focus on kidney transplant recipients (KTRs). Methods This single-center retrospective study included 313 cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…We found that both being on VGCV prophylaxis at infection onset and the exposure to low levels of VGCV were associated with CMV resistance: patients presenting refractory infection in this particular setting should be considered as more at risk of genotypically resistant infection. We also found significantly more patients with a history of VGCV prophylaxis in the R group: pre-emptive strategy could reduce resistance development through reduced GCV exposure [ 5 , 6 , 11 ], but CMV prophylaxis strategy did not result significative in multivariate analysis accordingly with the recent findings of Acquier et al [ 29 ] in a cohort of kidney transplant recipients. It has been known for a few years that VGCV exposure per se is not a risk factor for infection but that a longer exposure is associated with resistance development [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We found that both being on VGCV prophylaxis at infection onset and the exposure to low levels of VGCV were associated with CMV resistance: patients presenting refractory infection in this particular setting should be considered as more at risk of genotypically resistant infection. We also found significantly more patients with a history of VGCV prophylaxis in the R group: pre-emptive strategy could reduce resistance development through reduced GCV exposure [ 5 , 6 , 11 ], but CMV prophylaxis strategy did not result significative in multivariate analysis accordingly with the recent findings of Acquier et al [ 29 ] in a cohort of kidney transplant recipients. It has been known for a few years that VGCV exposure per se is not a risk factor for infection but that a longer exposure is associated with resistance development [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 80%
“…We also found significantly more patients with a history of VGCV prophylaxis in the R group: pre-emptive strategy could reduce resistance development through reduced GCV exposure [ 5 , 6 , 11 ], but CMV prophylaxis strategy did not result significative in multivariate analysis accordingly with the recent findings of Acquier et al [ 29 ] in a cohort of kidney transplant recipients. It has been known for a few years that VGCV exposure per se is not a risk factor for infection but that a longer exposure is associated with resistance development [ 29 , 30 ]. The threshold of exposure is usually recognized as 6 weeks [ 1 ] but a recent study found a threshold of 8 weeks of treatment with active replication as a risk factor [ 29 ] rather than prophylaxis itself or the cumulated time on prophylaxis and curative treatment Finally, the potential effect of VGCV exposure on resistance development should be balanced with the effects of more episodes of CMV replication in patients with pre-emptive strategies (immune exhaustion and opportunistic infections for instance).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…To assess the dose–response relationship, CMV viral load was divided into three categories: (1) 125–500 IU/mL, (2) 501–1000 IU/mL, and (3) more than 1000 IU/mL. The lowest threshold of 125 IU/mL arises from the lower limit of quantification of the assay used; the upper threshold of 1000 IU/mL was chosen based on the earlier cut-off for pre-emptive therapy initiation [ 26 , 27 ]. The pre-emptive antiviral therapy was applied once DNAemia exceeded 125 IU/mL and was continued until CMV DNA was undetectable in two consecutive samples taken within two weeks.…”
Section: Methodsmentioning
confidence: 99%
“…CDV is a cytidine monophosphate analogue and a competitive inhibitor of the viral DNA polymerase that undergoes phosphorylation using cell kinase so that the resistance mutations can be detected in the UL54 gene. It is also reserved for second-line treatments due to its considerable toxicity [ 27 , 28 ].…”
Section: Hcmv Antiviral Therapymentioning
confidence: 99%